Pengaruh Model Problem-Based Learning dengan Video Riil Kejadian IPA terhadap Scientific Reasoning Skills Siswa SMP - Sofiatul Mukarromah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Scientific reasoning skills are instrumental to a student's success in science, involving various logical thinking skills accompanied by scientific evidence. In reality, many students struggle to implement scientific knowledge when confronted with real-life situations. Based on this, this study focuses on determining students' scientific reasoning skills and the effect of the problem-based learning model with real science videos on students' scientific reasoning skills. This study used a quasi- experimental design with subjects divided into experimental and control groups. A scientific reasoning test instrument was used as the primary data source, supported by data from interviews, observations, and documentation. The collected data were then statistically analyzed using Microsoft Excel and the t-test. The findings revealed that the overall level of students' scientific reasoning achievement after the treatment was in the good category, although it needed to be optimized in terms of variable control reasoning. The results also prove the real impact of the problem- based learning model on students' scientific reasoning skills with a p-value of < 0.001. The results indicate that the PBL model combined with real science videos can help develop most aspects of students' scientific reasoning and become an adaptive strategy for teachers to create more meaningful learning for students.
FINALISASI oleh Arif 2026 Mei 20
Keywords: problem-based learning; real science video; scientific reasoning skills